Penyakit Bercak Kuning Ubi Jalar di Bogor, Jawa Barat - Anastasya Hondo; Kartika Catur Damaiyanti; Muhammad Fikri Hafizh; Niky Elfa Amanatillah; Tri Asmira Damayanti (Jurnal Fitopatologi Indonesia, 2018)
Yellow Spot Disease on Sweet Potato in Bogor, West JavaYellow spot symptom on sweet potato red cultivar was observed in Cikarawang and Leweung kolot area, Bogor regency. Symptomatic leaf samples gave positive reaction in serological detection by DIBA method using polyclonal antiserum for Potyvirus. DNA fragment of ± 700 bp in length was successfully amplified by RT-PCR using degenerate primer for cylindrical inclusion gene (CI) of Potyvirus.  Further nucleotide sequence analysis indicated high homology to Sweet potato feathery  mottle virus (SPFMV). The homology of SPFMV Cikarawang (Crkw) isolate ranging from 89–98% to several isolates from other countries with the highest homology to Japan and Spain isolates. SPFMV Crkw isolate was in the same cluster with the Japan and Spain isolates based on phylogenetic analysis of both nucleotide and amino acid sequences. This is the first report of SPFMV on sweet potato in Bogor, West Java, Indonesia.